Effect of Six Week Yogic Exercise on Physical Fitness of Standard-V Students. - Mondal, Tirtha; Biswas, Malabika (International Research Journal of Ayurveda & Yoga, 2023)
Yoga is a multifaceted spiritual tool with enhanced health and well-being as one of its positive effects. Physical fitness is not only of the most important keys to healthy body, it is the basis of dynamic and creative intellectual activity. Promoting physical fitness of young and older adults is essential in reducing healthcare expenditures which would occur in the future for those with chronic health problems. The relationship between soundness of the body and the activities of the mind is subtle and complex. Yoga is a discipline to improve or develop one’s inherent power in a balanced manner. It offers the means to attain complete self realization. Yoga and Physical fAim: To find out the effect of yogic exercise on physical fitness of class-V students. Variables: Height, Weight, Body Mass Index (BMI), Speed, Physical Fitness Index (PFI), Blood Pressure (BP) were measured to find out the correlation among pre and post situation. Results: Height, PFI and Systolic blood pressure were found positively significant in 0.05 level after six-week yogic training Conclusions: short term of yogic training may reduce disease risk factor and may improve the lifestyle. itness are two keys for good performance in day-to-day life.